Transmission lowers US generation costs, but generator incentives are not aligned - Dasom Ham; Owen Kay; Catherine Hausman (Proceedings of the National Academy of Sciences, 2026)
The US electricity grid is rapidly evolving with the entry of low-cost renewable electricity. As a result, new supply is not spatially matched to demand, and the transmission network has become more strained. Better market integration could thus lower US generation costs. We document that eliminating interregional constraints would have reduced electricity generation costs across the lower US 48 states by $5.8 to 7.1 billion in 2022 and $3.4 to 5.0 billion in 2023. But market integration creates winners and losers among generation companies, and we show that producers in some regions have incentives to delay or block grid integration despite the overall system benefits.